2009
DOI: 10.1152/ajplung.00491.2007
|View full text |Cite
|
Sign up to set email alerts
|

Trauma-hemorrhagic shock-induced pulmonary epithelial and endothelial cell injury utilizes different programmed cell death signaling pathways

Abstract: Intestinal ischemia after trauma-hemorrhagic shock (T/HS) results in gut barrier dysfunction and the production/release of biologically active and tissue injurious factors in the mesenteric lymph, which, in turn, causes acute lung injury and a systemic inflammatory state. Since T/HS-induced lung injury is associated with pulmonary endothelial and epithelial cell programmed cell death (PCD) and was abrogated by mesenteric lymph duct ligation, we sought to investigate the cellular pathways involved. Compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…Although different from the cell death patterns observed during LPS-induced lung injury, hyperoxia and ischemia-reperfusion injury are the main causes of complex cell death that include apoptosis, oncosis, and necrosis [20,21] . Dimtrios and colleagues have suggested that two programmed cell death pathways exist in the lungs in rat models of trauma-hemorrhagic shock [22] . These two pathways involve endothelial cell death via a caspase-independent way and epithelial cell apoptosis through a caspase-dependent pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Although different from the cell death patterns observed during LPS-induced lung injury, hyperoxia and ischemia-reperfusion injury are the main causes of complex cell death that include apoptosis, oncosis, and necrosis [20,21] . Dimtrios and colleagues have suggested that two programmed cell death pathways exist in the lungs in rat models of trauma-hemorrhagic shock [22] . These two pathways involve endothelial cell death via a caspase-independent way and epithelial cell apoptosis through a caspase-dependent pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic injury represents a leading cause of critical illness, and respiratory failure is a common complication of severe trauma [1]. Approximately 2% to 4% of persons with trauma develop acute lung injury (ALI).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, focal chest trauma, whether blunt or penetrating, heightens the risk for ALI [4,5]. Similarly, the presence of hemorrhagic shock along with its treatment can potentiate ALI [1,6]. Thus, one aspect of trauma resuscitation, namely, blood transfusion, is independently linked to the development of ALI.…”
Section: Introductionmentioning
confidence: 99%
“…Small intestinal ischemia-reperfusion (IIR) injury can occur at great number of pathophysiologic conditions, including hemorrhagic shock [1,2] and acute mesenteric ischemia [3], which becomes one of most common clinical events. In addition to the local injury, IIR can also result in severe injury of remote tissues and concomitant distant organ dysfunction [4], especially affects the lungs, which accounts for the high mortality.…”
Section: Introductionmentioning
confidence: 99%